Prevalence of repeat breeding in cattle - KUMAR, PAWAN; ROY, G P; AKHTAR, M H; PRASAD, K M; SINGH, A P (The Indian Journal of Animal Reproduction, 2023)
The prevalence of repeat breeding fyndrome in 973 cattle in Patna, Bihar, was analysed. The overall prevalence of repeat breeding recorded was 12.02 %. Months and seasons did not have any significant influence on the occurrence ofrepeat breeding condition.